Knowledge of COVID-19 and Death Toll Cases in Manipur - , H. Sorojini Devi; , K. Somarani Devi; , Th. Kanon Devi; , Ak. Bojen Meetei (Archives of Current Research International, 2020)
Background: The disease Covid-19 has led to a great loss of million people worldwide and this disease is caused by a novel virus called SARS-CoV-2. Objective: The objective of the present study aims at examining the knowledge of Coronavirus disease (COVID -19) among the participants and the death toll cases in Manipur. Setting: The study was conducted in the campuses of Dhanamanjuri Colleges of Arts, Science and Commerce, Dhanamanjuri University, Imphal, Manipur. Subjects and Methods: A total of 200 participants (boys=110 and girls =90) aged 20-30 years was considered for this present study. Data were collected using interview schedule containing Covid -19 related variables. Design: The design of the present study is based on Cross-sectional method. Results: Results indicated that maximum participants (83.5%) considered Covid-19 as virus, 1.0% thought as bacteria, but 15.5% knew that Covid -19 is a disease. A very high percentage of students (95.5%) knew the various symptoms of the disease. Amongst them, 92.5% of participants also knew the mode of transmission of the novel Virus. However, 4.5% and 8.5% of them had incomplete knowledge about of the mysterious novel coronavirus disease symptoms and its mode of transmission. While maintaining the preventive measures, 10.5% of participants used masks irregularly in the public places. As well as, only 34.0% of respondents kept masks inside the pocket or bag, and 5.5% of the subjects didn’t have the idea of washing hands or sanitisation. It was also found among the participants that some of them (30.0%) were aware of testing to know the status of Covid-19 and the number of confirmed cases was 8.0%. From the above results, it may be said that there was lack of proper knowledge among some section of the participants. The lack of proper knowledge of any novel fatal disease or virus and its related preventive measures are major risks to the whole public. However, immune responds can play role in defending the risk of the disease.